A IMPLEMENTASI EKONOMI SYARIA'H : MARKETING SYARI'AH: “STRATEGI ADAPTASI UMKM TERHADAP TRANSFORMASI PENJUALAN DIGITAL” : STUDI KASUS PERCETAKAN TAHTA GRAFIKA DI KENDAL - Husna, Fina (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2025)
In the fast-paced digital era, adaptation is the key to the success of MSMEs in maintaining their existence. Changes in consumer behavior that are shifting to digital platforms require business actors to develop online marketing strategies. However, not all MSME actors are able to adapt optimally due to limitations in digital literacy, human resources, and infrastructure. This study aims to analyze the adaptation strategy of MSMEs to the shift in the market from conventional to digital, with a case study on the Tahta Grafika printing MSME in Boja District, Kendal Regency. The study used a qualitative approach through in-depth interviews with business owners. The results show that Tahta Grafika has implemented an effective marketing strategy using various stages such as market segmentation strategy, target market determination strategy, positioning strategy or determining market position by utilizing online ordering services via WhatsApp and marketing via Facebook Marketplace. This strategy is considered effective in maintaining local customer loyalty because it is also strengthened by a CRM strategy, but has not reached the national market due to limited professional digital personnel. Therefore, interventions in the form of digital training, recruitment of skilled workers, and support from local governments are needed so that MSMEs are able to compete in the digital ecosystem.